Aplikasi ekstrak asam sunti sebagai bahan penggumpal dan karakterisasi fisik keju oles dengan variasi jenis bahan baku santan kelapa dan jenis starter cultures - Dewi Yunita; Syarifah Rohaya; Tyas Dwi Rahayu; Putu Virgina Partha Devanthi; Kurnia Ramadhan (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Coconut milk-based spreadable cheese has been developed in previous studies with the addition of 1% starter culture (Lactococcus lactis subsp lactis, Lactococcus lactis subsp. cremoris, and Lactococcus lactis subsp. lactis biovar. diacetylactis) to replace the use of milk. However, the texture of the spreadable cheese melts easily at room temperature. This research aims to improve the physical characteristics of spreadable cheese made from coconut milk. Improvements were made by adding asam sunti extract, a local commodity from Aceh Province. Spreadable cheese is then made from various types of raw materials (B; 100% pure coconut milk (B1) and 50% pure coconut milk + 50% water (B2)) and various types of starter culture (S; freeze-dried (S1) and cultured (S2)). The resulting spreadable cheese was analyzed for physical characteristics (spreadability, texture, meltability, and oil separation index). The results showed that the combination of treatment with variations in the type of raw material and type of starter culture did not affect the spreadability of coconut milk spread cheese (P0.05). The spreadable cheese made from 50% pure coconut milk + 50% water and cultured starter (B2S2) is more recommended for commercial production. This cheese has a spreadability value of 7.50 ± 0.50 cm, texture of 3.50 ± 0.00 gf, meltability of 15.33 ± 2.00 mm, and oil separation index of 87.33 ± 8.62%